2015
DOI: 10.1186/s12913-015-1254-9
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare seeking behaviour among self-help group households in Rural Bihar and Uttar Pradesh, India

Abstract: BackgroundIn recent years, supported by non-governmental organizations (NGOs), a number of community-based health insurance (CBHI) schemes have been operating in rural India. Such schemes design their benefit packages according to local priorities. This paper examines healthcare seeking behaviour among self-help group households with a view to understanding the implications for the benefit packages offered by such schemes.MethodsWe use cross-sectional data collected from two of India’s poorest states and estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

40
342
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 226 publications
(387 citation statements)
references
References 34 publications
40
342
5
Order By: Relevance
“…As demonstrated in this study, effective engagement of communities in quality care improvement could help enhance perceived quality of healthcare and promote good health seeking behavior of clients. This observation is consistent with conclusions in the AU Policy Brief Report [24] and some studies on Ghana [2123] which intimated that, active involvement of communities in health programmes improves experiences of health staff and clients of service quality in health facilities.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As demonstrated in this study, effective engagement of communities in quality care improvement could help enhance perceived quality of healthcare and promote good health seeking behavior of clients. This observation is consistent with conclusions in the AU Policy Brief Report [24] and some studies on Ghana [2123] which intimated that, active involvement of communities in health programmes improves experiences of health staff and clients of service quality in health facilities.…”
Section: Discussionsupporting
confidence: 92%
“…Even though the other quality healthcare components also improved, the marginal increases were lower. These findings are consistent with arguments that active involvement of communities is a potential avenue to enhance mutual collaboration between healthcare providers and clients towards quality service improvement [8, 19, 23, 24]. When healthcare providers reckon they are closely monitored by their communities, they are more likely to demonstrate greater accountability to clients [23].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the case of abortion, courtesy stigma is the name-calling or discrediting of individuals (in this case, health care providers) as a result of their association with women who request or are in need of abortion or TOP services [42]. In Ghana, a 2016 study also found that courtesy stigma resulted in health care provider reluctance to provide TOP [22]. In the USA, Harris et al advanced the concept of courtesy stigma by describing both the negative stereotypes of abortion providers and the multiple levels at which providers experience stigma, as well as developing tools to measure abortion stigma [43].…”
Section: Discussionmentioning
confidence: 99%
“…Research on abortion has focused on: the legal and ethical standards for protecting women’s human rights [1416]; global and regional estimates of the incidence of unsafe abortion and associated mortality [4,6]; the relationship between induced abortion and adverse psychological outcomes among women undergoing the procedure [17]; conscientious objection and health care providers’ attitudes towards TOP services [16,18]; and strategies to reduce the incidence of unintended pregnancy and unsafe abortion [19]. Studies among health care providers have reported feelings of anxiety, professional ambivalence and conscientious objection, experiences of courtesy stigma and discrimination, violence or fear of violence, often resulting in health care providers not talking about their work or not advocating for the provision of TOP services, and fear of being labelled or rejected [2022]. These negative emotions or experiences are exacerbated by health system deficiencies, insufficient or lack of peer support, lack of understanding of the consequences of stigma for abortion providers, potential risks of the procedure, and request for abortion from women with advanced pregnancies [14,23,24].…”
Section: Introductionmentioning
confidence: 99%